Possible Influences of Endogenous and Exogenous Ligands on the Evolution of Human Siglecs - Angata, Takashi (Frontiers in Immunology, 2018)
Sialic acids, a group of acidic sugars abundantly expressed in the tissues of deuterostome animals but rarely found in microbes, serve as a "signature of self" for these animals. Cognate sensors for sialic acids include Siglecs, a family of transmembrane lectins of vertebrate immune systems that recognize glycans containing sialic acids. A type of sialic acid called N-glycolylneuraminic acid (Neu5Gc) is abundant in many mammalian lineages including great apes, the closest extant relatives of modern human, but was lost in the lineage leading to modern human via the pseudogenization of the CMAH gene encoding the enzyme that converts N-acetylneuraminic acid (Neu5Ac) to Neu5Gc. Loss of Neu5Gc appears to have influenced the evolution of human Siglecs, such as the adjustment of sialic acid binding preferences and the inactivation of at least one Siglec. In addition, various mechanistic studies using model systems and genetic association studies have revealed that some human Siglecs interact with pathogens and influence the outcome of infections, and these pathogens in turn likely influence the evolution of these Siglecs. By understanding the evolutionary forces affecting Siglecs, we shall achieve a better appreciation of Siglec functions, and by understanding Siglec functions, we can obtain deeper insight into the evolutionary processes driving Siglec evolution.